A comparative case study on time management of fourth year high school students - Brasales, Noricar N.; Nicor, Joan B.; Portillo, Sharon Rose P.; Sancio, Jenalyn F. (2000.)
Executive summary-The research is a comparative case study on time management of fourth year high school students enrolled in public and private schools in both rural and urban areas. The researchers aimed to find out the factors that influenced the time management of fourth year hig school students. The respondnets were fourth year high school students of St. Catherine Parochial School in Leon, Iloilo, Leonora S. Salapantan National High School in Iloilo City. The method used in data gathering was through questionnaires. The study was descriptive hence descriptive statistics was used. After a through analysis of the data gathered, the findings revealed that the factors that afeect time management of fourth year high school students are school population, family income and family composition.
Research Paper (Mgt 200-Management Research). -- [Iloilo City] : University of the Philippines in theVisayas -College of Management, March 2000.